Gavagai Is as Gavagai Does: Learning Nouns and Verbs From Cross‐Situational Statistics. (18th October 2014) - Monaghan, Padraic; Mattock, Karen; Davies, Robert A. I.; Smith, Alastair C.
Abstract Learning to map words onto their referents is difficult, because there are multiple possibilities for forming these mappings. Cross‐situational learning studies have shown that word‐object mappings can be learned across multiple situations, as can verbs when presented in a syntactic context. However, these previous studies have presented either nouns or verbs in ambiguous contexts and thus bypass much of the complexity of multiple grammatical categories in speech. We show that noun word learning in adults is robust when objects are moving, and that verbs can also be learned from similar scenes without additional syntactic information. Furthermore, we show that both nouns and verbs can be acquired simultaneously, thus resolving category‐level as well as individual word‐level ambiguity. However, nouns were learned more quickly than verbs, and we discuss this in light of previous studies investigating the noun advantage in word learning.